Microbially mediated silicon-based agro-wastes: a possible option in reducing bioaccumulation of arsenic - Koley, Sabyasachi; Garg, Jancy; Golui, Krisanu; Rakshit, Amitava (Frontiers in Nutrition, 2025)
BackgroundArsenic (As), a class I carcinogen, affected 200 million people globally either through consumption of contaminated groundwater or food crops especially rice, leading to acute or chronic health issues including fatigue, respiratory diseases, liver fibrosis, and cancer.Research gapFor reclamation, majority of the efforts focused on single application of a particular amendment in reducing As levels in rice ecosystems.MethodologyThis particular article comprehensively studied package of those amendments being used in reducing the bioaccumulation of As.ResultsConsortia based package involving Si-rich agro-wastes (intact waste, compost, ash etc.) and agriculturally important microbes have the potential to reduce translocation of As to the above ground biomass by various mechanisms viz., competitive inhibition of transporters, iron plaque formation, anti-oxidant defense system, microbial oxidation etc. Rice straw compost (RSC) and husk composts (RHC) which are rich sources of Si (7–10%), Fe (700–900 ppm), Zn (40–60 ppm) and P (0.35–0.5%) have been explored owing the ability of Si and P to hinder the uptake of highly toxic As (III) and As (V) within plants by competitively inhibiting LSi1 and LSi2 for Si, and Pht4 and Pht8 transporters for P uptake with additional Fe released from amendments can form Fe-plaques that might work like As filters. Agro-wastes combined with silicate solubilizing bacteria significantly reduced As loading in final produce (25–52%), thereby reducing dietary exposure (ADI) even up to one third compared to control.ConclusionThis comprehensive review on understanding and validation of the mechanism provides a valuable insight in formulating a feasible As toxicity management strategy.